2022
DOI: 10.1177/0271678x221142533
|View full text |Cite
|
Sign up to set email alerts
|

Putative neurochemical and cell type contributions to hemodynamic activity in the rodent caudate putamen

Abstract: Functional magnetic resonance imaging (fMRI) is widely used by researchers to noninvasively monitor brain-wide activity. The traditional assumption of a uniform relationship between neuronal and hemodynamic activity throughout the brain has been increasingly challenged. This relationship is now believed to be impacted by heterogeneously distributed cell types and neurochemical signaling. To date, most cell-type- and neurotransmitter-specific influences on hemodynamics have been examined within the cortex and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“…Glucose is essential for the synthesis of the glutamate-precursor glutamine [ 97 ], and alcohol misuse has been linked to a deficit in extracellular glutamate levels and an altered balance between the glutamate-dependent excitatory and GABA-dependent inhibitory neurotransmission systems [ 98 , 99 ]. Nevertheless, it should be noted that decrease in neuronal activity or glucose metabolism does not necessarily come with a decrease in FC (i.e., enhanced synchronization can occur at lower amplitude of activity), and involvement of vasoactive neurotransmission can lead to decoupling between neuronal activity and flow [ 60 , 100 , 101 ]. In a recent study, Ochi and colleagues (2022) reported an inverted correlation between alcohol-induced increase in cortical FC and somatostatin cortical gene expression in human brain, suggesting that alcohol-induced inhibition of GABAergic interneurons might underly the change in connectivity [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose is essential for the synthesis of the glutamate-precursor glutamine [ 97 ], and alcohol misuse has been linked to a deficit in extracellular glutamate levels and an altered balance between the glutamate-dependent excitatory and GABA-dependent inhibitory neurotransmission systems [ 98 , 99 ]. Nevertheless, it should be noted that decrease in neuronal activity or glucose metabolism does not necessarily come with a decrease in FC (i.e., enhanced synchronization can occur at lower amplitude of activity), and involvement of vasoactive neurotransmission can lead to decoupling between neuronal activity and flow [ 60 , 100 , 101 ]. In a recent study, Ochi and colleagues (2022) reported an inverted correlation between alcohol-induced increase in cortical FC and somatostatin cortical gene expression in human brain, suggesting that alcohol-induced inhibition of GABAergic interneurons might underly the change in connectivity [ 83 ].…”
Section: Discussionmentioning
confidence: 99%